Harassment and Bullying among Students in Higher Education Institutions: Manifestation of Single Cases of Harassment and Bullying in Aspects of Demographic Variables - Jolita Vveinhardt; Vilija Bite Fominiene; Regina Andriukaitiene; Dalia Streimikiene (Amfiteatru Economic)
The research goal - to analyse manifestations of single cases of harassment and bullying in students' inter-relationship and to compare them in aspects of socio-demographic variables. 623 students studying at Lithuanian higher education institutions were questioned. We determined a dependence of harassment and bullying on respondents' age: they were experienced more often by 18-30 year-old students, whereas older students' complaints were less. Older students more often requested for active policy of higher education institutions in preventing negative relations. Women showed more initiative in seeking for help, unlike men, experience of negative relations of which was higher in the past. Harassment and bullying were more experienced by the students studying at higher education colleges, unlike those studying at universities. The research results are significant in striving for better perception of impact of harassment and bullying at higher education institutions on demographic variables and negative inter-personal relationship experienced at school age. This knowledge is necessary for higher education institutions preparing and developing a prevention of harassment and bullying.